Difficult texts: Matthew 23 - Duffield, Ian K. (Theology, 2020)
Some Gospel verses have been criticized for engaging in hate speech or for being anti-Semitic: for example, the blood libel in Matthew and the categorization of Jews as of the devil' in John. However, the woes that Jesus declares upon scribes and Pharisees have received less attention. Although Matthew 23 is vulnerable to the accusation that it is anti-Semitic hate speech and should not be used in church, the criticism is misplaced as anachronistic and insensitive to the realities of the times and to the role the woes play in a prophetic critique of religious professionals. Furthermore, criticisms of the rhetoric tend to ignore the direction of the text against self-righteousness, including our own.